The Effect of Consuming Groundnuts on Serum Testosterone Levels and Lipid Profile in Male Rats (Tanzania Medical Journal, 2015)
Introduction: Groundnuts (Arachis hypogaea) are used by people for nutritional, medicinal, and recreational purposes. The aim of this study was to establish the effect of consuming groundnut (Arachis hypogaea) on serum testosterone level and lipid profile in male rats.Methods: Wistar male rats (n=32) aged 8-10 weeks were randomly divided into four groups of eight rats each: groups II, III and IV were fed diet containing 25%, 50% and 75% groundnuts, respectively. Group I which served as control was fed on normal commercial rat feed. At the end of twenty days blood was withdrawn, and sera harvested. Total testosterone radioimmunoassay and biochemical analysis were done. Statistical analysis was performed using STATA. Student`s t-test and Wilcoxon rank-sum test were used to compare testosterone and lipids levels between groups, and level of significance was fixed at p=0.05.Results: The rats fed on 25% groundnuts showed insignificant difference in mean lipids and testosterone p>0.05. The 75% groundnuts fed rats had significantly lower total cholesterol, higher high density lipoprotein-cholesterol and higher testosterone p<0.05, an insignificantly higher low density lipoprotein-cholesterol plus a higher level of triglycerides p>0.05 while 50% groundnut fed rats had significantly higher levels of the parameters p<0.05 compared to the control except for low density lipoprotein-cholesterol.Conclusion: The results showed that groundnuts significantly increased testosterone accompanied with increased high density lipoprotein-cholesterol levels when fed on rat feed containing 50% and 75% groundnuts. This suggests that groundnuts may be a potential solution to age related decline in testosterone production.